Meta-analysis of the best exercise mode and dose study for improving spinal health - Li, Ziyang; Bao, Zihan; Wang, Shun; Zhao, Mengqi (Frontiers in Sports and Active Living, 2025)
ObjectiveTo explore the influence of different exercise methods on spinal health through Meta-analysis, and then provide scientific exercise suggestions for different groups of people.MethodsRandomized controlled experimental studies (RCTs) of different exercise modes on spinal health in CNKI, Wanfang, Web of Science, PubMed, and Ebsco databases were searched. The search dates were limited to self-built databases until February 2025. After screening, 30 articles and 2,105 subjects were included and analyzed using Review Manager 5.4 and Stata 18 software.ResultsExercise therapy was significantly superior to the control group in relieving pain (SMD = −0.87, 95% CI: −1.11, −0.63), improving cervical spine dysfunction (SMD = −0.90, 95% CI: −1.47, −0.34), improving lumbar spine dysfunction (SMD = −0.59, 95% CI: −0.77, −0.41) and correcting scoliosis (SMD = −0.82, 95% CI: −1.30, −0.34). Through subgroup analysis of heterogeneous sources from seven aspects: disease type, intervention site, intervention mode, intervention time, intervention frequency, intervention period and age,the results show that exercise intervention can effectively improve the pain level and dysfunction in patients with spinal diseases, and help to promote the recovery of Cobb's angle in patients. Subgroup analysis showed that each intervention of 10–30 min, 3–4 times a week and continuous exercise for 10–20 weeks was an ideal exercise plan.ConclusionExercise intervention can significantly improve the health of spinal patients, and the 18-style of Zong Jianji has strong universality and is suitable for the intervention of various spinal diseases. The ideal exercise program is 10–30 min each intervention, 3–4 times a week, and continuous exercise for 10–20 weeks. Baduanjin has better curative effect on patients with low back pain and scoliosis. Each intervention lasts for 30–50 min, exercises 3 times a week or 1–2 times a day, and continuous exercise for 5–6 weeks or 10 weeks is the most practical. In the future, more high-quality, multi-disease clinical studies and evidence should be collected to verify this conclusion.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier [CRD420251008053].